Protective effect of cannabinoid type II receptor ligand on bleomycin-induced pulmonary fibrosis in mice - Cheng Cao; Run-Lin Wang; Chen-xin Guo; Xiao-wei Xu; Jia-hui Wei; Wen-zhuo Cheng; Yi-zhe Yu; Jia-jie Shi; Zhi-wei Feng; Yan Chen (PLoS ONE, 2026)
This study aimed to investigate the protective effects of the CB2R ligand compound COCA (N-(3-chloro-2-methylphenyl)-5-(4-hydroxyphenyl)-1,2-oxazole-3-carboxamide) against bleomycin (BLM)-induced pulmonary fibrosis in mice. Compound COCA was identified via AI-driven virtual screening from the ChEMBL database. Forty male C57BL/6J mice were randomly divided into five groups: control, model (BLM), low-dose COCA, high-dose COCA, and pirfenidone. Pulmonary fibrosis was induced by intratracheal BLM administration in the model and treatment groups. Pathological evaluation, ELISA, immunofluorescence, and Western blot were conducted.The results showed that COCA significantly alleviated BLM-induced inflammation and fibrosis. ELISA demonstrated decreased serum levels of TNF-α and IL-6 in the treated groups compared to the BLM group ( P < 0.01). Immunofluorescence indicated reduced expression of Col-I and Col-III in the treated groups ( P < 0.01). Western blot analysis revealed an upregulation of CB2R in the BLM group, and enhanced expressions of Nrf2 and Smad7 in the treated groups ( P < 0.01).In conclusion, AI-driven virtual screening enabled the identification of the CB2R ligand COCA, which binds to CB2R, activates the Nrf2/Smad7 pathway, downregulates related cytokines, and plays a therapeutic and protective role in pulmonary fibrosis.